Topic: social and cultural barriers with regards to diabetes prevention in the province of Carchi - Ecuador - Salgado Jiménez, Ruth (SATHIRI, 2019)
Diabetes Mellitus (DM) is a chronic disease that disseminates fast degrading hope and quality of life of those who suffer it, their families and population in general. Unfortunately it is a degenerative disease, which has deep complications that cause premature death. Governments develop great economic efforts to promote and prevent this disease, however, it is not enough and every year the number of people who suffer from it is multiplied. The regimes through their ministries of health and social welfare allocate large amounts of money to prevent the development of this disease. In spite of this, there are great economic, social, cultural and psychological barriers that influence negatively, therefore, the promotion and prevention of this disease have not had success on population. One of the functions of the nursing professionals is education or counseling. This function allows working with users in promotion and prevention. However, there are social and cultural limitations that prevent the counseling process achieves the expected results. A baseline is drawn up starting from an interview with 100 nurses from the Centers and sub-centers of health in Carchi Province, with the respective instrument, to determine what these barriers are. In addition, 40 diabetic people are interviewed to confront the information. The results found that the main social barriers that predispose to a series of behaviors related to health-disease are: age, education and employment status. While the cultural barriers defined as the values, beliefs, attitudes and ideals that prevent them from establishing an assertive relationship with users are: customs, myths and education.